Singing The Glory Down : Amateur Gospel Music in South Central Kentucky, 1900-1990 - Montell, William Lynwood, 1931- (Book collections on Project MUSE., 1991)
In Singing the Glory Down, William Lynwood Montell contributes to a fuller understanding of twentieth-century American culture by examining the complex relationships between gospel music and the culture of the nineteen-county study area in which this music has flourished for a hundred years. He has recorded the memories and feelings of those who were young while the movement gathered steam and who remember it at its high point, and stories about those who have passed over that river about which they loved to sing. In the early 1900s, a singing school or gospel convention was a major social eve.